Geotecnologias como subsídio ao planejamento ambiental integrado do município de Barroquinha, Ceará - Brasil - Rabelo, Francisco Davy Braz (2018)
Integrated analysis is the fundamental methodological approach for the establishment of environmental planning and management strategies. The diagnosis provided by the integrated analysis subsidizes subsequent stages of environmental planning and management, which is necessary for the combination of technical works, political administrative support and community participation. Analysis and planning, in municipal scale, considering the municipality of Barroquinha, are an example of the application of the methodology. Geotechnologies have been perfecting, with technological innovations, at increasingly efficient levels of precision as a resource for reading and interpreting terrestrial reality. Possibilities for carrying out space-time readings with satellite images and quantification of spatial dynamics have brought significant advances in environmental planning, whether in the elaboration of diagnostics, management plans, as well as in the definition of forecasts and the creation of probable landscape scenarios futures. The general objective of this research is to present the applications of Geotechnology as a subsidy to integrated environmental planning, in the municipality of Barroquinha, located in the north-west of the state of Ceará, in the Northeast region of Brazil, using the methodological approach of Geoecology of Landscapes, aiming to cover, socioenvironmental diagnosis, multiple natural and anthropic factors that directly or indirectly influence the dynamics of environmental systems and the quality of life in multiple diversity. some features / integrated analysis. A proposal was developed for environmental / geoecological and functional / propositional zoning planning of local character, that is, aimed at the municipality and community, seeking the institution of a model of, which subsidize the implementation of program and projects for community and participatory management.